(untitled) (مجلة جامعة اللاذقية - سلسلة العلوم الصحية, 2019)
This study aims to identify the attitude of the 4th grade students of the Faculty of Physical Education towards the profession of teaching. Descriptive method with survey style is used on the sample of the study that contains all the 4th grade students in Faculty of Physical Education 2017/2018. A questionnaire is distributed on the sample. The study concluded that there are no significant differences in attitude towards the profession of teaching between males and female students;and results showed a general weak attitude toward the profession of teaching in the sample of the study. هدف الدراسة هو التعرف على اتجاهات طلبة السنة الرابعة بكلية التربية الرياضية في جامعة تشرين نحو مهنة التعليم حيث استخدمت الباحثة لتحقيق هذا الهدف المنهج الوصفي بأسلوب المسح على عينة البحث المكونة من كافة طلبة السنة الرابعة في كلية التربية الرياضية للعام الدراسي 2017/2018 حيث قامت الباحثة بتوزيع استبانة على أفراد العينة، وقد توصلت الدراسة أنه لا توجد فروق ذات دلالة إحصائية لدى طلبة السنة الرابعة بكلية التربية الرياضية في جامعة تشرين بحسب متغير الجنس، حيث تبين ان اتجاهات كل من الطلاب والطالبات منخفضة بشكل عام.